Acupuncture for the treatment of severe acute pain in Herpes Zoster: results of a nested, open-label, randomized trial in the VZV Pain Study - Placido Giuseppina; Consorte Augusta; Toro Patrizia; Di Profio Sonia; Congedo Gabriele; Rebuzzi Cristina; Polilli Ennio; Manzoli Lamberto; Tontodonati Monica; Ursini Tamara; Laganà Stefano; D'Amario Claudio; et al. (BMC, 2011)
Abstract Background Data on the potential efficacy of acupuncture (AC) in controlling intense or very intense pain in patients with Herpes Zoster (HZ) has not been so far adequately assessed in comparison with standard pharmacological treatment (ST) by a controlled trial design. Methods Within the VZV Pescara study, pain was assessed in HZ patients on a Visual Analogue Scale (VAS) and by the McGill Pain Questionnaire (MPQ) both at the beginning and at the end of treatment. Response rates, mean changes in pain intensity, differences in total pain burden with an area-under-the-curve (AUC) method over a 1-year follow-up and differences in the incidence of Post-Herpetic Neuralgia (PHN) were evaluated. Results One hundred and two patients were randomized to receive either AC (n = 52) or ST (n = 50) for 4 weeks. Groups were comparable regarding age, sex, pain intensity at presentation and missed antiviral prescription. Both interventions were largely effective. No significant differences were observed in response rates (81.6% vs 89.2%, p = 0.8), mean reduction of VAS (4.1 +/- 2.3 vs 4.9 +/- 1.9, p = 0.12) and MPQ scores (1.3 +/- 0.9 vs 1.3 +/- 0.9, p = 0.9), incidence of PHN after 3 months (48.4% vs 46.8%, p = 0.5), and mean AUC during follow-up (199 +/- 136 vs 173 +/- 141, p = 0.4). No serious treatment-related adverse event was observed in both groups. Conclusions This controlled and randomized trial provides the first evidence of a potential role of AC for the treatment of acute herpetic pain. Trial registration ChiCTR-TRC-10001146.